2022
DOI: 10.1002/glia.24325
|View full text |Cite
|
Sign up to set email alerts
|

Human myeloid progenitor glucocorticoid receptor activation causes genomic instability, type 1 IFN‐ response pathway activation and senescence in differentiated microglia; an early life stress model

Abstract: One form of early life stress, prenatal exposure to glucocorticoids (GCs), confers a higher risk of psychiatric and neurodevelopmental disorders in later life. Increasingly, the importance of microglia in these disorders is recognized. Studies on GCs exposure during microglial development have been limited, and there are few, if any, human studies. We established an in vitro model of ELS by continuous pre-exposure of human iPS-microglia to GCs during primitive hematopoiesis (the critical stage of iPS-microglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…TSPO structure representation is shown on the top right (structure adapted from Guo et al [ 57 ]). HiPSC and patient monocyte microglia show increased IFN-γ signalling upon glucocorticoid exposure [ 211 ] and increased synaptic uptake compared to control lines, respectively [ 172 ]. b Drawing of 3D microglial morphology in a control brain (left) and a schizophrenia brain (right).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TSPO structure representation is shown on the top right (structure adapted from Guo et al [ 57 ]). HiPSC and patient monocyte microglia show increased IFN-γ signalling upon glucocorticoid exposure [ 211 ] and increased synaptic uptake compared to control lines, respectively [ 172 ]. b Drawing of 3D microglial morphology in a control brain (left) and a schizophrenia brain (right).…”
Section: Introductionmentioning
confidence: 99%
“…While hiPSC-derived microglia have been used to study neurodegenerative disorders [ 82 , 177 , 190 ], few studies to date have harnessed this model for SZ research. A study modelling early-life stress by exposing microglial precursors to glucocorticoids found that an increased type I interferon signalling and cellular senescence in the matured cells [ 211 ]. Another study differentiated patient iPSCs to neurons but derived microglia from patient monocytes instead [ 172 ].…”
Section: Introductionmentioning
confidence: 99%
“…In response to chronic stress, microglia appear to be reactive and exhibit elevated levels of Iba-1, a protein involved in cytoskeletal movements, CD11b, a beta- integrin that is upregulated in reactive cells, and CD68, a lysosomal protein of microglia that is considered a marker for phagocytosis [ 33 , 34 ]. Moreover, microglia in particular, but also astrocytes, are involved in immune responses and neuroinflammatory processes that are altered in numerous stress-related neurological and psychiatric disorders, including PTSD [ 15 , 17 , 18 , 35 38 ]. Although the involvement of astrocytes and microglia has been documented in animal models of chronic stress that reproduce depression-like behaviors, their role in the acute stress response remains poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…In response to chronic stress, microglia appear to be reactive and exhibit elevated levels of Iba-1, a protein involved in cytoskeletal movements, CD11b, a beta-integrin upregulated in reactive cells, and CD68, a microglial lysosomal protein considered a marker of phagocytosis [26,27]. Moreover, microglia in particular, but also astrocytes, are involved in immune responses and neuroin ammatory processes that are altered in numerous stress-related neurological and psychiatric disorders, including PTSD [28][29][30][31]. Although the involvement of astrocytes and microglia has been documented in animal models of chronic stress that reproduce depression-like behaviors, their role in the acute stress response remains poorly studied.…”
Section: Introductionmentioning
confidence: 99%